马来西亚华语电影和短片的语码转换、语码混合以及词汇借用（2004—2010）= Code switching, code mixing and borrowing in Malaysia Chinese movies and short films (2004–2010) - 张玮峻 Chong, Wai Jiunn (2011)
马来西亚由多元民族所组成，其社会结构自然也比较复杂。经过长时间的相处和马来西亚政府成立后对于国语马来语的推广，各民族之间的交流逐渐变得简单。语码转换、语码混合和词汇借用在语言学界逐渐受到学者们的重视，因为在这个科技不断进步以致人与人的交流不断增进的年代，文化和语言的交流促成了很多语码转换、语码混合和词汇借用的例子。本文选择马来西亚的电影或短片的对白作为研究语码转换、语码混合和词汇借用的语料，时间限制在2004年到2010年之间，一共选择了8部电影和19部短片。Malaysia is a multi-racial society, which means the social structure is more complex compare with some other country. After a long period of coexistence and the Malaysian government’s promotion of the learning of national language, Malay Language, the communication between different ethnic groups gradually become easier. Code switching, code mixing and lexical borrowing are common issue of some society and this catches the attention of linguistic researcher. As in the age of advanced technology which accelerates the communication efficiency between people around the world, exchange of culture and language led to the example of code switching, code mixing and lexical borrowing keep increasing. This paper chooses the dialogues of Malaysian movies or short films as the data of research to get a rough idea of Malaysian's code switching, code mixing and lexical borrowing, time limit sets between 2004 and 2010, in total, 8 movies and 19 short films had been selected.